Integral methanol-to-hydrogen catalyst for vehicle as well as preparation method and application of integral methanol-to-hydrogen catalyst

The integrated methanol hydrogen production catalyst for automotive prepared by performing hydrothermal reaction on the entire metal frame and combining the calcination and reduction steps, the problems of degradation of performance and structural rupture in vehicle-mounted applications are solved, and high mechanical strength and stability are achieved.

CN119549153APending Publication Date: 2025-03-04FZU ZIJIN HYDROGEN POWER TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411551795.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing methanol hydrogen production catalyst for automotive is difficult to adapt to the frequent fluctuations in high and low temperatures, mechanical vibration, large airspeed changes and stability requirements of automobiles, resulting in degradation of catalyst performance and structural rupture.

Method used

The whole metal frame is used as a support to grow the catalyst precursor in situ on the surface of the metal frame through hydrothermal reaction, and the integrated methanol hydrogen production catalyst for automotive is prepared in combination with the calcination and reduction steps.

Benefits of technology

It improves the mechanical strength and catalytic stability of the catalyst, can effectively resist temperature fluctuations, mechanical vibrations and spacespeed changes, avoid the decline in activity caused by carbon deposits, and significantly improves the stability of catalytic performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides an integral methanol-to-hydrogen catalyst for a vehicle as well as a preparation method and application thereof, and the preparation method comprises the following steps: firstly, cleaning a metal framework in an ultrasonic environment, cleaning the metal framework again with distilled water after cleaning, and drying; mixing the dried metal framework with an aqueous solution of alkali carbonate, and keeping for at least 10 hours in a high-temperature and high-pressure environment with the temperature of more than 120 DEG C and the pressure of more than 1 MPa; cooling to room temperature, washing with distilled water, and drying to obtain a catalyst precursor; finally, roasting the obtained catalyst precursor in an air atmosphere; and after roasting, reducing in a reducing atmosphere to obtain the integral methanol-to-hydrogen catalyst for vehicles. The prepared catalyst does not need secondary forming, the preparation method is simple, the catalyst has extremely high structural strength, the reaction performance cannot be reduced along with air speed change, meanwhile, good catalytic performance can still be kept under long-time reaction, and the catalyst is very suitable for vehicle-mounted application scenes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of methanol cracking hydrogen production, and in particular to a vehicle-used integral methanol hydrogen production catalyst and a preparation method and application thereof. Background Art

[0002] With the development of science and technology, transportation has become the third largest energy-consuming industry in the world after industry and construction. At present, automobile fuel is mainly based on oil resources. However, with the increasing demand for oil in various industries, the shortage of oil is becoming increasingly serious. Compared with traditional fuels, methanol has the advantages of storage and transportation, high energy conversion efficiency, and is a H 2 Methanol is a good carrier of CO and is considered to be the most promising alternative fuel for automobiles in the future. The effect of using methanol directly as a fuel is not ideal, mainly due to its low calorific value per unit volume, large latent heat of vaporization, and low braking efficiency. If the waste heat of exhaust gas is used to gasify methanol and convert it into hydrogen-rich gas with the vehicle and then used as engine fuel, the thermal efficiency of the engine can be greatly improved and the emission of NOx, HC, etc. in exhaust gas can be greatly reduced. Therefore, how to continuously and stably decompose methanol into CO and H 2 , efficient catalyst is the key.

[0003] At present, the main catalyst for methanol to hydrogen production is SiO 2 、ZrO 2 As carriers, active components are introduced by impregnation, and the structure is mostly powder. However, vehicle-mounted scenarios have higher requirements for catalysts: (1) The waste heat temperature of automobile exhaust is high and unstable, and vehicle-mounted catalysts must be able to avoid breakage caused by frequent fluctuations in high and low temperatures; (2) The car vibrates greatly during driving, and the vehicle-mounted catalyst should have extremely high mechanical strength; (3) The speed of the car changes all the time during driving, and the airspeed also changes, requiring the vehicle-mounted catalyst to have the ability to adapt to high airspeed processing; (4) It has high stability to avoid the problem of decreased activity caused by carbon deposition. However, existing automotive catalysts are all powder catalysts that are extruded and molded under high pressure, and this type of catalyst is difficult to meet the above vehicle-mounted requirements. Therefore, it is necessary to develop a catalyst with high mechanical strength, good performance and high stability. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the technical problem in the prior art that traditional powder catalysts formed through molding are difficult to adapt to vehicle-mounted application scenarios, thereby providing a vehicle-use integral methanol hydrogen production catalyst and its preparation method and application, thereby improving the mechanical strength and catalytic stability of the catalyst.

[0005] The technical solution adopted by the present invention to solve its technical problem is: a preparation method of an integral methanol hydrogen production catalyst for vehicle, comprising the following steps: S1: cleaning a metal skeleton in an ultrasonic environment, and after cleaning, cleaning the metal skeleton again with distilled water and drying it; S2: mixing the dried metal skeleton with an alkali metal carbonate aqueous solution, and keeping it in a high temperature and high pressure environment with a temperature greater than 120°C and a pressure greater than 1MPa for at least 10 hours; then cooling to room temperature, cleaning with distilled water and drying to obtain a catalyst precursor; S3: calcining the obtained catalyst precursor in an air atmosphere; S4: reducing the calcined catalyst precursor in a reducing atmosphere to obtain an integral methanol hydrogen production catalyst for vehicle.

[0006] Furthermore, in S1, the metal skeleton is placed in a dilute hydrochloric acid solution for ultrasonic cleaning for 10 minutes; in S2, the dried metal skeleton is mixed with an alkali metal carbonate aqueous solution in a high temperature and high pressure environment with a temperature above 120 to 180°C and a pressure greater than 1MPa for 10 to 48 hours, then cooled to room temperature and taken out, washed with distilled water and dried to obtain a catalyst precursor.

[0007] Furthermore, in S2, the concentration of the alkali metal carbonate aqueous solution is in the range of 0.1 to 1.5 mol / L. Furthermore,

[0008] Furthermore, the alkali metal carbonate aqueous solution is any one or more of lithium carbonate solution, sodium carbonate solution, potassium carbonate solution, rubidium carbonate solution, cesium carbonate solution, francium carbonate solution, lithium bicarbonate solution, sodium bicarbonate solution, potassium bicarbonate solution, rubidium bicarbonate solution, cesium bicarbonate solution and francium bicarbonate solution.

[0009] Furthermore, in S3, the catalyst precursor is calcined in an air atmosphere at a temperature range of 150-300°C for 0.5-8 hours; in S4, the calcined catalyst precursor is reduced in a reducing atmosphere at a temperature range of 150-300°C for 0.5-8 hours to obtain an automotive integral methanol hydrogen production catalyst.

[0010] Furthermore, the reducing atmosphere is a hydrogen atmosphere or a mixed gas atmosphere consisting of hydrogen and nitrogen.

[0011] A vehicle-use integral methanol-to-hydrogen catalyst prepared by a method for preparing a vehicle-use integral methanol-to-hydrogen catalyst comprises a metal skeleton containing active components and loaded with alkali metals; the mass fraction of the active components is 10-30%, and the mass fraction of the alkali metals is 0.1-0.5%.

[0012] Furthermore, the metal skeleton is any one or more of brass, copper, nickel silver and bronze.

[0013] Furthermore, the morphological structure of the metal skeleton is any one or more of foam, fiber, fiber felt, wire mesh, round tube, round disc or particle, and the porosity of the metal skeleton ranges from 50 to 300 PPI.

[0014] Application of an integral methanol hydrogen production catalyst for vehicles, the integral methanol hydrogen production catalyst for vehicles is suitable for a reaction temperature of 350°C and a mass space velocity of 1-4h -1 On-vehicle methanol cracking reaction to produce hydrogen.

[0015] The technical solution of the present invention has the following advantages:

[0016] 1. The vehicle-use monolithic methanol-to-hydrogen catalyst provided by the present invention does not require secondary molding and has a simple preparation method. The catalyst uses a monolithic metal as a skeleton carrier, grows a catalyst precursor in situ on the surface of the metal skeleton through a hydrothermal reaction, and finally obtains the catalyst through calcination reduction.

[0017] 2. The catalyst provided by the present invention uses a monolithic metal as a carrier, which has excellent heat transfer performance and can effectively avoid temperature fluctuations caused by frequent changes in operating conditions during driving, thereby further preventing the catalyst from cracking due to thermal expansion and contraction. In addition, the catalyst of the present invention has excellent structural strength and can effectively prevent the catalyst from being rubbed and crushed due to large vibrations of the car during driving.

[0018] 3. The catalyst provided by the present invention adopts a large-porosity monolithic metal as a carrier, has excellent mass transfer performance, can better adapt to the changes in air velocity caused by frequently changing working conditions during driving, and avoids the performance degradation of traditional catalysts at high air velocity due to poor mass transfer performance.

[0019] 4. The catalyst provided by the present invention has high porosity, which reduces the residence time of the product on the catalyst surface and prevents the product CO from further undergoing disproportionation reaction and carbon deposition on the surface, thereby causing poor stability. DETAILED DESCRIPTION

[0020] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0022] The present application discloses a method for preparing a vehicle-use integral methanol-to-hydrogen catalyst, comprising the following steps:

[0023] S1: cleaning the metal skeleton in an ultrasonic environment to remove the oxide layer on the metal surface, and then washing the metal skeleton again with distilled water, and then drying it;

[0024] S2: mixing the dried metal skeleton with an alkali metal carbonate aqueous solution, and maintaining the mixture in a high temperature and high pressure environment with a temperature greater than 120° C. and a pressure greater than 1 MPa for at least 10 hours; then cooling the mixture to room temperature, washing the mixture with distilled water, and drying the mixture to obtain a catalyst precursor;

[0025] S3: calcining the obtained catalyst precursor under air atmosphere;

[0026] S4: reducing the calcined catalyst precursor under a reducing atmosphere to obtain a vehicle-use integral methanol-to-hydrogen catalyst.

[0027] In S1, a metal skeleton is placed in a dilute hydrochloric acid solution for ultrasonic cleaning, wherein the ultrasonic cleaning time is 10 minutes; to remove the oxide layer on the metal surface, the metal skeleton is cleaned again with distilled water and dried after cleaning; wherein the manufacturing material of the metal skeleton is any one or more of brass, copper, nickel silver or bronze, the morphological structure of the metal skeleton is any one or more of foam, fiber, fiber felt, wire mesh, round tube, disc or particle, and the porosity range of the metal skeleton is 50 to 300 PPI; by using the above-mentioned monolithic metal with a larger porosity as a carrier, the heat and mass transfer performance of the catalyst is improved, and at the same time, the porosity range is limited to the range of 50 to 300 PPI, while ensuring excellent heat and mass transfer performance, ensuring that the reaction gas can pass through the catalyst during the reaction, and taking into account the catalytic performance.

[0028] In S2, the alkali metal carbonate aqueous solution is prepared by dissolving any one or more of alkali metal carbonates, such as lithium carbonate, sodium carbonate, potassium carbonate, rubidium carbonate, cesium carbonate, francium carbonate, lithium bicarbonate, sodium bicarbonate, potassium bicarbonate, rubidium bicarbonate, cesium bicarbonate and francium bicarbonate in distilled water; transferring the prepared alkali metal carbonate aqueous solution to a high-pressure environment with a pressure greater than 1 MPa, such as a high-pressure reactor; then placing the cleaned and dried metal skeleton in the alkali metal carbonate aqueous solution; placing the mixed solution in a temperature range of 120 to 180°C The catalyst precursor is obtained by hydrothermally reacting an alkali metal carbonate aqueous solution with a metal skeleton to obtain a catalyst precursor. More specifically, the concentration range of the alkali metal carbonate aqueous solution is 0.1 to 1.5 mol / L. The catalyst precursor is prepared by hydrothermally reacting an alkali metal carbonate aqueous solution with a metal carrier, which can change the electronic structure of the prepared catalyst, facilitate the subsequent adsorption and activation of methanol for decomposition, and improve the catalytic performance.

[0029] In S3, the catalyst precursor is calcined in an air atmosphere at a temperature range of 150 to 300° C. for 0.5 to 8 hours; in S4, the calcined catalyst precursor is reduced in a reducing atmosphere at a temperature range of 150 to 300° C. for 0.5 to 8 hours to obtain an integral methanol hydrogen production catalyst, wherein the reducing atmosphere is a hydrogen atmosphere, or a mixed gas atmosphere consisting of hydrogen and nitrogen.

[0030] The present application also discloses a vehicle-use integral methanol hydrogen production catalyst prepared by the preparation method of the vehicle-use integral methanol hydrogen production catalyst, comprising a metal skeleton, wherein the metal skeleton is any one or more of brass, copper, nickel silver and bronze; the morphological structure of the metal skeleton is any one or more of foam, fiber, fiber felt, wire mesh, round tube, disc or particle, and the porosity of the metal skeleton ranges from 50 to 300 PPI; the vehicle-use integral methanol hydrogen production catalyst is suitable for a reaction temperature of 350°C and a mass space velocity of 1-4 h -1 On-vehicle methanol cracking reaction to produce hydrogen.

[0031] The vehicle-use monolithic methanol-to-hydrogen catalyst and the preparation method thereof are further described below through examples and comparative examples.

[0032] Example 1

[0033] The embodiment of the present invention provides a method for preparing an integral methanol-to-hydrogen catalyst, and the specific steps and parameters are as follows:

[0034] At room temperature, 1 g of brass foam was ultrasonically treated in a dilute hydrochloric acid solution for 10 min to remove the copper oxide layer on the surface, then washed with distilled water and dried;

[0035] 6.9 g of potassium carbonate was dissolved in 50 ml of distilled water, and the prepared solution was transferred into a high-pressure reactor. 1 g of washed foam brass was weighed and placed in the solution. The solution was kept at 140° C. for 24 hours. After cooling, the solution was taken out, washed with distilled water, and then dried to obtain a catalyst precursor.

[0036] The catalyst precursor was calcined at 300°C for 2 hours in an air atmosphere, and finally reduced at 300°C for 4 hours in a hydrogen-nitrogen mixed gas atmosphere (hydrogen gas volume fraction 2%) to obtain a monolithic methanol-to-hydrogen catalyst. 2 -TPR) measurement shows that in the catalyst prepared in this example, the mass content of K is 0.2%, and the mass content of the active component Cu is 25%.

[0037] Example 2

[0038] The embodiment of the present invention provides a method for preparing an integral methanol-to-hydrogen catalyst, and the specific steps and parameters are as follows:

[0039] At room temperature, 1 g of white copper fiber was ultrasonically treated in a dilute hydrochloric acid solution for 10 min to remove the surface copper oxide layer, then washed with distilled water and dried;

[0040] 3.5 g of sodium carbonate was dissolved in 50 ml of distilled water, and the prepared solution was transferred into a high-pressure reactor. 1 g of washed white copper fiber was weighed and placed in the solution. The solution was kept at 120° C. for 10 hours. After cooling, the fiber was taken out, washed with distilled water, and then dried to obtain a catalyst precursor.

[0041] The catalyst precursor was calcined at 200°C for 8 hours in an air atmosphere, and finally reduced at 200°C for 8 hours in a hydrogen-nitrogen mixed gas atmosphere (hydrogen gas volume fraction 2%) to obtain an integral methanol-to-hydrogen catalyst. 2 -TPR measurement shows that in the catalyst prepared in this example, the mass content of Na is 0.1%, and the mass content of the active component Cu is 20%.

[0042] Example 3

[0043] The embodiment of the present invention provides a method for preparing an integral methanol-to-hydrogen catalyst, and the specific steps and parameters are as follows:

[0044] At room temperature, 1g of copper wire mesh was ultrasonically treated in a dilute hydrochloric acid solution for 10 min to remove the surface copper oxide layer, then washed with distilled water and dried;

[0045] 10.4 g of lithium carbonate was dissolved in 50 ml of distilled water, and the prepared solution was transferred into a high-pressure reactor. 1 g of cleaned copper wire mesh was weighed and placed in the solution, and kept at 150° C. for 10 hours. After cooling, it was taken out, washed with distilled water, and then dried to obtain a catalyst precursor.

[0046] The catalyst precursor was calcined at 250°C for 2 hours in an air atmosphere, and finally reduced at 250°C for 2 hours in a hydrogen-nitrogen mixed gas atmosphere (hydrogen gas volume fraction 2%) to obtain an integral methanol-to-hydrogen catalyst. 2 -TPR measurement shows that in the catalyst prepared in this example, the mass content of Li is 0.5%, and the mass content of the active component Cu is 30%.

[0047] Example 4

[0048] The embodiment of the present invention provides a method for preparing an integral methanol-to-hydrogen catalyst, and the specific steps and parameters are as follows:

[0049] At room temperature, 1 g of bronze disc was ultrasonically treated in a dilute hydrochloric acid solution for 10 min to remove the copper oxide layer on the surface, then washed with distilled water and dried;

[0050] 0.7 g of cesium carbonate was dissolved in 50 ml of distilled water, and the prepared solution was transferred into a high-pressure reactor. 1 g of a cleaned bronze disc was weighed and placed in the solution, and kept at 180°C for 12 hours. After cooling, it was taken out, washed with distilled water, and dried to obtain a catalyst precursor.

[0051] The catalyst precursor was calcined at 300°C for 8 hours in an air atmosphere, and finally reduced at 300°C for 8 hours in a hydrogen-nitrogen mixed gas atmosphere (hydrogen gas volume fraction 2%) to obtain an integral methanol-to-hydrogen catalyst. 2 -TPR measurement shows that in the catalyst prepared in this example, the mass content of Cs is 0.2%, and the mass content of the active component Cu is 10%.

[0052] Example 5

[0053] The embodiment of the present invention provides a method for preparing an integral methanol-to-hydrogen catalyst, and the specific steps and parameters are as follows:

[0054] At room temperature, 1 g of brass fiber was ultrasonically treated in a dilute hydrochloric acid solution for 10 min to remove the copper oxide layer on the surface, then washed with distilled water and dried;

[0055] 3.5 g of potassium carbonate was dissolved in 50 ml of distilled water, and the prepared solution was transferred into a high-pressure reactor. 1 g of cleaned brass fiber was weighed and placed in the solution, and kept at 120° C. for 48 hours. After cooling, the fiber was taken out, washed with distilled water, and then dried to obtain a catalyst precursor.

[0056] The catalyst precursor was calcined at 300°C for 6 hours in an air atmosphere, and finally reduced at 300°C for 6 hours in a hydrogen-nitrogen mixed gas atmosphere (hydrogen gas volume fraction 2%) to obtain an integral methanol-to-hydrogen catalyst. 2 -TPR measurement shows that in the catalyst prepared in this example, the mass content of Na is 0.5%, and the mass content of the active component Cu is 25%.

[0057] Comparative Example 1

[0058] At room temperature, 1 g of brass foam was ultrasonically treated in a dilute hydrochloric acid solution for 10 min to remove the copper oxide layer on the surface, then washed with distilled water and dried;

[0059] Weigh 1 gram of washed brass foam and place it in 50 milliliters of distilled water, transfer it into a high-pressure reactor, keep it at 140° C. for 24 hours, take it out after cooling, wash it with distilled water, and then dry it to obtain a catalyst precursor;

[0060] The catalyst precursor was calcined at 300° C. for 2 hours in an air atmosphere, and finally reduced at 300° C. for 4 hours in a hydrogen-nitrogen mixed gas atmosphere (hydrogen gas volume fraction 2%) to obtain an integral methanol-to-hydrogen catalyst.

[0061] Comparative Example 2

[0062] At room temperature, an aqueous solution containing 0.7 g of copper nitrate and 0.035 g of potassium carbonate was prepared and reacted with 1 g of commercial SiO 2 The carrier was impregnated with equal volume; calcined at 300°C for 2 hours in an air atmosphere, and finally reduced at 300°C for 4 hours in a hydrogen-nitrogen mixed gas atmosphere (hydrogen gas volume fraction 2%) to obtain a powdered methanol hydrogen production catalyst.

[0063] Experimental Example 1

[0064] The methanol hydrogen production catalysts prepared in Examples 1-5 and Comparative Examples 1-2 were subjected to a methanol decomposition activity test, and 0.5 g of the monolithic catalyst and the powder catalyst were weighed for performance evaluation, wherein the structure of the powder catalyst was a catalyst formed by sieving through a 30-60 mesh sieve. The two catalysts were tested as follows: the reaction temperature was 350°C, and the mass space velocity was 1-4 h -1 , at an airspeed of 4h -1 The catalytic performance at reaction times of 10 hours and 200 hours was measured, and the results are shown in Table 1. In addition, 1 g of all catalysts were weighed for ultrasonic treatment, and the structural strength of the catalysts was determined by mass loss, and the results are shown in Table 2.

[0065] Table 1. Methanol conversion rates of the methanol to hydrogen catalysts prepared in Examples 1-5 and Comparative Examples 1-2 at different space velocities and methanol conversion rates at different reaction times at the same space velocity

[0066] <![CDATA[1 a ]]> <![CDATA[4 a ]]> <![CDATA[4 b ]]> Example 1 97% 96% 96% Example 2 90% 90% 90% Example 3 82% 81% 81% Example 4 85% 85% 85% Example 5 92% 91% 91% Comparative Example 1 20% 20% 20% Comparative Example 2 80% 69% 58%

[0067] a Conversion rate at 10 hours reaction time; b The conversion rate after reaction time of 200 hours.

[0068] Table 2. Mass of methanol to hydrogen catalysts prepared in Examples 1-5 and Comparative Example 2 after ultrasonic treatment for different time periods

[0069] 0 hours 10 hours 100 hours Example 1 1 gram 0.97 g 0.96 g Example 2 1 gram 0.95 g 0.93 g Example 3 1 gram 0.94 g 0.93 g Example 4 1 gram 0.96 g 0.95 g Example 5 1 gram 0.95 g 0.94 g Comparative Example 2 1 gram 0.88 g 0.62 g

[0070] As shown in Table 1, Examples 1-6 exhibited high methanol decomposition activity at different space velocities, while the catalyst prepared in Comparative Example 1 had low activity, which illustrates the advanced nature of the preparation method provided by the present invention, and the catalyst prepared in this manner using brass foam as a carrier had the highest methanol decomposition activity. By comparing the performance of Examples 1-6 and Comparative Example 2 at different space velocities and at different reaction times at the same space velocity, it can be seen that the catalyst prepared by the present invention exhibits stable performance, will not be attenuated by changes in space velocity, and will not attenuate as the reaction time increases, which illustrates that the catalyst prepared by the present invention has good reaction performance stability.

[0071] As can be seen from Table 2, by comparing the mass table of Examples 1-6 and Comparative Example 2 at different ultrasonic times, the catalyst prepared by the present invention has undergone long-term vibration, and the mass remains basically unchanged, indicating that the monolithic catalyst has extremely strong mechanical properties. The above results fully prove that the catalyst prepared by the present invention can be well applied to the scene of hydrogen production by decomposition of methanol for vehicles.

[0072] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the present invention.

Claims

1. A method for preparing a vehicle-use monolithic methanol-to-hydrogen catalyst, characterized in that: The steps include: S1: cleaning the metal frame in an ultrasonic environment, washing the metal frame again with distilled water, and drying the metal frame after washing; S2: mixing the dried metal skeleton with an alkali metal carbonate aqueous solution, and maintaining the mixture in a high temperature and high pressure environment with a temperature greater than 120° C. and a pressure greater than 1 MPa for at least 10 hours; then cooling the mixture to room temperature, washing the mixture with distilled water, and drying the mixture to obtain a catalyst precursor; S3: calcining the obtained catalyst precursor under air atmosphere; S4: reducing the calcined catalyst precursor under a reducing atmosphere to obtain a vehicle-use integral methanol-to-hydrogen catalyst.

2. The method for preparing a vehicle-use monolithic methanol-to-hydrogen catalyst according to claim 1, characterized in that: In S1, the metal skeleton is placed in a dilute hydrochloric acid solution for ultrasonic cleaning for 10 minutes; in S2, the dried metal skeleton is mixed with an alkali metal carbonate aqueous solution in a high temperature and high pressure environment with a temperature above 120 to 180° C. and a pressure greater than 1 MPa for 10 to 48 hours; then, it is cooled to room temperature and taken out, washed with distilled water, and then dried to obtain a catalyst precursor.

3. The method for preparing the vehicle-use integral methanol-to-hydrogen catalyst according to claim 1, characterized in that: In S2, the concentration of the alkali metal carbonate aqueous solution is in the range of 0.1 to 1.5 mol / L.

4. The method for preparing a vehicle-use monolithic methanol-to-hydrogen catalyst according to claim 1, characterized in that: The alkali metal carbonate aqueous solution is any one or more of lithium carbonate solution, sodium carbonate solution, potassium carbonate solution, rubidium carbonate solution, cesium carbonate solution, francium carbonate solution, lithium bicarbonate solution, sodium bicarbonate solution, potassium bicarbonate solution, rubidium bicarbonate solution, cesium bicarbonate solution and francium bicarbonate solution.

5. The method for preparing a vehicle-use monolithic methanol-to-hydrogen catalyst according to claim 1, characterized in that: In S3, the catalyst precursor is calcined in an air atmosphere at a temperature range of 150-300°C for 0.5-8 hours; in S4, the calcined catalyst precursor is reduced in a reducing atmosphere at a temperature range of 150-300°C for 0.5-8 hours to obtain an integral methanol hydrogen production catalyst for vehicles.

6. The method for preparing the vehicle-use monolithic methanol-to-hydrogen catalyst according to claim 5, characterized in that: The reducing atmosphere is a hydrogen atmosphere or a mixed gas atmosphere consisting of hydrogen and nitrogen.

7. A vehicle-use monolithic methanol-to-hydrogen catalyst prepared by the method for preparing a vehicle-use monolithic methanol-to-hydrogen catalyst according to any one of claims 1 to 6, characterized in that: It comprises a metal skeleton, wherein the metal skeleton contains active components and the metal skeleton is loaded with alkali metal; the mass fraction of the active components is 10-30%, and the mass fraction of the alkali metal is 0.1-0.5%.

8. The vehicle-use monolithic methanol-to-hydrogen catalyst according to claim 7, characterized in that: The metal skeleton is any one or more of brass, copper, nickel silver and bronze.

9. The monolithic methanol to hydrogen catalyst according to claim 8, characterized in that: The morphological structure of the metal skeleton is any one or more of foam, fiber, fiber felt, wire mesh, round tube, round piece or particle, and the porosity of the metal skeleton ranges from 50 to 300 PPI.

10. Use of the vehicle-use integral methanol-to-hydrogen catalyst according to any one of claims 7 to 9, characterized in that: The vehicle-use integral methanol hydrogen production catalyst is suitable for a reaction temperature of 350°C and a mass space velocity of 1-4h -1 On-vehicle methanol cracking reaction to produce hydrogen.